INDICATORS OF HOMEOSTASIS IN ASSESSING THE EFFICIENCY OF HUMAN ADAPTATION TO HIGH MOUNTAINS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
27 male residents of low mountains aged 20-22 years were examined in low mountains, after moving them to high mountains and after returning to low mountains. The studies were carried out on a portable analyzer of gases and electrolytes of blood Abbott I-STAT. It was noted that the partial pressure and saturation of oxygen in the conditions of high mountains decreased, and the partial pressure of carbon dioxide and pH of arterial blood increased. In the process of readaptation, these indicators did not differ from those obtained before climbing the mountains. The concentration of hemoglobin in the conditions of high mountains and in the process of readaptation increased in comparison with the data obtained before climbing the mountains. The concentration of HCO3- and titratable blood bases increased in high altitude conditions. In the process of readaptation, the concentration of HCO3-blood remains increased. The concentration of sodium ions in highlands increased and the concentration of potassium, calcium and chlorine ions decreased. In the process of readaptation, the concentration of potassium and chloride ions remains lower, while the concentration of calcium ions does not differ.
Keywords: adaptation, high mountains, readaptation, partial voltage and saturation of oxygen, partial pressure of carbon dioxide, electrolytes.